Interest in paromomycin for the treatment of visceral leishmaniasis (kala-azar) - Wiwanitkit V (Dove Medical Press, 2012)
Viroj Wiwanitkit1–31Wiwanitkit House, Bang Khae, Bangkok, Thailand; 2Hainan Medical University, Haikou, Hainan, People's Republic of China; 3Joseph Ayo Babalola University, Ikeji-Arakeji, Osun State, NigeriaAbstract: Leishmaniasis is an important vector-borne disease, and it is classified as one of the most important tropical fly-borne infections. This disease can cause two types of clinical manifestations: cutaneous forms and visceral forms. Visceral leishmaniasis, which is also called kala-azar, is a very serious infection that can be fatal. The management of visceral leishmaniasis requires informed diagnostic and therapeutic approaches. Continuous research and development regarding the treatment of visceral leishmaniasis had led to many improvements. Paromomycin is a relatively new antibiotic drug that has been used for the treatment of visceral leishmaniasis for several years. This article reviews and discusses the use of paromomycin for visceral leishmaniasis therapy.Keywords: visceral, leishmaniasis, paromomycin